2012
DOI: 10.1007/s00467-012-2276-8
|View full text |Cite
|
Sign up to set email alerts
|

Long-term eculizumab improves clinical outcomes in atypical hemolytic uremic syndrome

Abstract: Background Atypical hemolytic uremic syndrome (aHUS) is a rare genetic disorder caused by chronic uncontrolled complement activation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(34 citation statements)
references
References 9 publications
3
29
0
2
Order By: Relevance
“…That eculizumab may be efficacious to rescue central nervous system involvement is suggested by nine case reports, including four in children [87,90,110,[123][124][125][126][127]. Eculizumab also appeared lifesaving in four children with myocardial involvement [83,90,92,110]. The reports of four children who developed cerebral ischemic events due to stenosis of cerebral arteries after several years on dialysis have suggested that local complement activation added to the vascular consequences of long-term dialysis may lead to such macrovascular complications [101,[128][129][130].…”
Section: Education Information Cardmentioning
confidence: 93%
“…That eculizumab may be efficacious to rescue central nervous system involvement is suggested by nine case reports, including four in children [87,90,110,[123][124][125][126][127]. Eculizumab also appeared lifesaving in four children with myocardial involvement [83,90,92,110]. The reports of four children who developed cerebral ischemic events due to stenosis of cerebral arteries after several years on dialysis have suggested that local complement activation added to the vascular consequences of long-term dialysis may lead to such macrovascular complications [101,[128][129][130].…”
Section: Education Information Cardmentioning
confidence: 93%
“…10 There are no randomized controlled trials examining the treatment of aHUS. There are small case reports and case series [11][12][13][14] and a prospective trial 15 of patients who were successfully treated with eculizumab. Evidence suggests that earlier treatment leads to greater improvement in renal function and reversal of target organ damage.…”
Section: Discussionmentioning
confidence: 99%
“…Case reports have been published with follow-up ranging from 1 to 3 years from initiation of treatment. 11,14 Respiratory tract infections, hypertension, and gastrointestinal disturbances are the most common adverse events reported, 16 and meningococcal septicemia has been described. 16,17 Administration of eculizumab in immunosuppressed patients may be complicated by meningococcal disease despite previous vaccination, 17 as described in our patient.…”
Section: Discussionmentioning
confidence: 99%
“…For atypisk hemolytisk uremisk syndrom er det ikke gjort randomiserte, placebokontrollerte studier, men det foreligger flere studier der effekt på endepunkter som nyrefunksjon og proteinuri er dokumentert (13,18). En rekke kasuistikker og serier med noen få pasienter har vist meget god effekt, noe som sammen med sykdommens sjeldne forekomst har lagt grunnlaget for myndighetenes godkjenning (19).…”
Section: Kontrollerte Kliniske Studierog Mangel På Slikeunclassified